Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde